EVALUATION OF LONG-TERM OUTCOMES FOR PENILE FRACTURES FOLLOWING IMMEDIATE VS. DELAYED SURGICAL REPAIR- A PROSPECTIVE STUDY. - Mishra, Sumanta Kumar; Panda, Sumit Kumar; Jagdev, Jagat Ballav; Kumar, Pabitra (Student's Journal of Health Research Africa, 2023)
Purpose: A penile fracture may affect erectile dysfunction (ED) and overall sexual satisfaction. This study aimed to compare the long-term effects of immediate versus delayed surgical repair of penile fractures on postoperative ED, fibrous tunica plaques, and chordee formation. Materials and Methods: This is a prospective observational study conducted over two years, which included patients with penile fracture. Details of injury, symptoms, treatment, and long-term outcomes (up to 12 months) were collected. Data were presented using summary statistics. Results: A total of 21 patients (early surgical repair [Group A], n = 13; delayed surgical repair [Group B], n = 8) were enrolled in this study. The common cause of penile fracture was masturbation (n1 = 5 [early presentation]; n2 = 5 [delayed presentation]) and sexual intercourse (n3 = 7 [early presentation]; n4 = 4 [delayed presentation]) in Groups A and B, respectively. Penile ecchymosis/swelling and pain were present in all the patients of Group A (n = 13), while typical pop-up sound was heard by eight patients (61.54%) of Group A and six patients (75.00%) of Group B. The most common reason for the delay in the presentation was fear/embarrassment (75.00%). Penile paresthesia (n = 2) and penile curvature (n = 3) were observed in Group A, while penile paresthesia (n = 3) was also reported in Group B. None of the patients from both groups reported ED. All three patients with urethral injury repaired had mild degree of ventral chordee with a satisfactory erection and a good penetration. Conclusion: The results showed that delayed repair did not affect the long-term outcome with no major impact on erectile function and overall sexual satisfaction.